Spaces of Ideal Convergent Sequences - M. Mursaleen; Sunil K. Sharma (The Scientific World Journal)
In the present paper, we introduce some sequence spaces using ideal convergence and Musielak-Orlicz function ℳ=Mk. We also examine some topological properties of the resulting sequence spaces.